Competition for Attention in the ETF Space. (4th August 2022) - Ben-David, Itzhak; Franzoni, Francesco; Kim, Byungwook; Moussawi, Rabih
Abstract: The interplay between investors' demand and providers' incentives has shaped the evolution of exchange-traded funds (ETFs). While early ETFs invested in broad-based indexes and therefore offered diversification at low cost, more recent products track niche portfolios and charge high fees. Strikingly, over their first 5 years, specialized ETFs lose about 30% (risk-adjusted). This underperformance cannot be explained by high fees or hedging demand. Rather, it is driven by the overvaluation of the underlying stocks at the time of the launch. Our results are consistent with providers catering to investors' extrapolative beliefs by issuing specialized ETFs that track attention-grabbing themes.